Coping Capacity Model on Landslide Response Using OLR - Apriani, Ani; Putra, Bayurohman Pangacella; Fahrurrozi, Muhammad Ikrom; Hentihu, Shintia Pratiwi (International Journal of Advanced Science Computing and Engineering, 2023)
The community's unpreparedness for landslides that often occur suddenly has a big impact. This is due to community's ignorance of the symptoms and preventive measures. The improvement coping capacity in landslide-prone areas is important to mitigate the disaster. It is important to know the Coping Capacity in order to give recommendation in improvement of community’s ability on landslide disaster. Thus, this study aims to construct the model coping capacity using Ordinal Logistic Regression (OLR).  The model is conducted using OLS by look at the influence of mitigation knowledge, action plans and local wisdom on general knowledge about risks and efforts to save from disasters. The primary data is taken from  Sidoharjo, Yogyakarta where  86,17 %  in high potential landslide to the total area is 1113,99 Ha. The results are two model logistic of the coping capacity. The first result is the risks disaster model logistic with chi-square deviance value is 74.085 and sign level is 0.99. The second is the effort to save from the disaster model logistic with with chi-square deviance value is 70.492 and sign level is 0.901.  It can be said that the model is well to be used to modelled the coping capacity in Sidoharjo which the most influential on risks and efforts to save from disasters are mitigation knowledge and action plans, respectively.